Timing of Primary PCI and Mortality in Acute Myocardial Infarction: Impact of Door to Balloon Time - Ullah, Ikram; Khan, Muhammad Idrees; Umar Farooq,; Orakzai, Muhammad Hafeez; Abid Ullah,; Ahmad, Sohail (Indus Journal of Bioscience Research, 2024)
Objective: This study aimed to evaluate the impact of door-to-balloon (DTB) time on mortality in patients with ST-segment elevation myocardial infarction (STEMI) treated with primary percutaneous coronary intervention (PCI) at Hayatabad Medical Complex, Peshawar.Methodology: A prospective cohort study was conducted with 400 patients divided into two DTB time groups: "